Effects of breed and early feeding on intestinal microbiota, inflammation markers, and behavior of broiler chickens - Marcato, Francesca; Schokker, Dirkjan; Kar, Soumya Kanti; Bossers, Alex; Harders, Frank; Rebel, Johanna M. J.; Jansen, Christine A.; van der Valk, Elianne; Kruijt, Leo; te Beest, Dennis Elbert; de Jong, Ingrid C. (Frontiers in Veterinary Science, 2024)
Recently, the Netherlands has shifted toward more welfare-friendly broiler production systems using slower-growing broiler breeds. Early post-hatch feeding (EF) is a dietary strategy that is currently used in commercial broiler production to modulate the gut microbiota and improve performance and welfare. However, there is a knowledge gap in how both breed and EF and their interplay affect gut microbiota composition and diversity, inflammatory status, and broiler behavior. Therefore, the aim of this study was to investigate the effects of breed (fast vs. slower-growing), EF, and their interaction on jejunum microbiota, inflammation, and behavior of broiler chickens. The study included a total of 416 Ross 308 and 416 Hubbard JA757 day-old male broiler chickens, observed until they were 37 days and 51 days old, respectively. Within each breed, one-half of the chickens received EF and the other half did not. A total of two chickens per pen were euthanized at two time points, that is, target body weight (BW) of 200 g and 2.5 kg, and jejunum samples were collected. The jejunum content samples (N = 96) were analyzed for their microbiota, whereas the jejunum tissue (N = 96) was used for the detection of mRNA levels of cytokines (IL-17, IL-22, and IFNγ). Two behavioral tests were performed to assess fear responses: (1) a novel environment test at a target BW of 200 g and (2) a tonic immobility test at a target BW of 2.5 kg. Breed affected the microbiota at a target BW of 2.5 kg (p = 0.04). A breed × EF interaction (p = 0.02) was present for IFNγ at a target BW of 200 g. During the novel environment test, Ross 308 chickens exhibited a shorter latency to vocalize and a higher number of vocalizations compared to Hubbard JA757 chickens (p < 0.05). Early-fed broiler chickens vocalized less compared to not early-fed chickens (Δ = −27.8 on average; p < 0.01). During the tonic immobility test, Hubbard JA757 chickens exhibited a shorter latency to stand compared to Ross 308 chickens. In conclusion, using a slower-growing breed has beneficial effects on gut microbiota and fear responses of broilers, especially at slaughter age, whereas EF seems to have an impact only at an early stage of the life of broilers.